Judicial Resolution of Hibah (Gift) over Encumbered Property: An Analysis of the Abdul Hamid Masidullah v. Norehan Abdul Jabbar Case - Noor Lizza Mohamed Said; Muhamad Mu'izz Abdullah; Adnan Mohamed Yusoff (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Ownership of a property is a crucial aspect in determining the validity of a hibah (gift) contract. Accordingly, the permissibility of gifting an asset that is still under financial institution collateral has been a subject of scholarly debate, particularly on whether such an asset constitutes absolute ownership by the donor. The appeal case of Abdul Hamid Bin Masidullah v. Norehan Binti Abdul Jabbar (Mal No. 08000-001-0014-2018) serves as a reference regarding the permissibility of hibah involving collateralised property. One of the arguments raised by the Appellant was that the hibah of a property still under the collateral of the Government of Malaysia's Housing Loan Division was invalid, as the gifted property was not deemed to be under the complete or absolute ownership of the donor. However, the Syariah Court of Appeal of the State of Perak, Malaysia, dismissed the appeal and upheld the decision of the Syariah High Court in Hibah Case No. 08100-044-0149-2015. The Court ruled that the gifted property constituted full ownership by the donor. Therefore, this article aims to examine and analyse the reasoning behind the Court of Appeal's judgment on this issue, based on scholarly opinions and juristic arguments (fuqaha). This study employs a qualitative analysis, focusing on the Syariah Court of Appeal case of Abdul Hamid Bin Masidullah v. Norehan Binti Abdul Jabbar (Mal No. 08000-001-0014-2018). Data were collected through critical document analysis of court judgments, legal provisions, and relevant fatwas, with sources selected based on strict reliability and relevance criteria. Thematic analysis was used to systematically compare and synthesize diverse juristic opinions, ensuring the findings are jurisprudentially robust and contextually relevant to Malaysia's Syariah context. The study found that the reasoning in this appellate case aligns with Islamic legal principles and does not exclusively adhere to the opinion of a single school of jurisprudence. Instead, the views of scholars from other schools of thought, beyond the Shafi'i madhhab, were also considered and utilized by the Court in accordance with the contextual needs of the case. This study contributes to the development of Islamic property law by clarifying the judicial reasoning applied in resolving disputes over hibah (gifts) involving encumbered property